Global higher integrability for a doubly nonlinear parabolic system - Herán, Andreas; Rainer, Rudolf (Nodea-Nonlinear Differential Equations and Applications, 2022)
In this paper we establish a higher integrability result up to the boundary of weak solutions to doubly nonlinear parabolic systems. We show that the spatial gradient of a weak solution with vanishing lateral boundary values is integrable to a larger power than the natural power p, where the statement holds for parameters in the subquadratic case max2nn+2,1<p≤2.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Doubly nonlinear parabolic system; Gradient estimates; Higher integrability; Intrinsic geometry